Cost comparison of hydropower options for rural electrification in Rwanda - Nsengiyumva, Anicet (Department of Electrical Engineering, 2016)
The decision to develop a hydropower plant depends on several factors, which cost is the most significant. This thesis, entitled "Cost comparison of hydropower options for rural electrification in Rwanda" intends to show that the use of a large number of mini hydropower plants for electrification of sparse rural areas in Rwanda is the least cost option when compared to installing either a single small or large hydropower plants. This is done by considering rural households to be randomly distributed and the model composed by 98 rural villages having three different population densities is used to test the validity of the hypothesis. Three different hydropower options providing the same level of service to rural households were used for the cost comparison. The relationship between the electrification cost per household versus the population density is deduced. Many distribution technologies can be used in rural areas and the accurate selection of the appropriate distribution technology is the main concern as it affects the cost of the whole distribution system. The rural network should be carefully designed so that the sizing of conductors to be used for LV and MV network is properly done at a low cost. The high distribution cost depends largely on the size of power to be delivered. Based on these findings, the cost comparison of mini, small and large hydropower schemes for rural electrification in Rwanda is discussed.